Development of Chitosan Nanoparticles as a Stable Drug Delivery System for Protein/siRNA - Haliza Katas; Maria Abdul Ghafoor Raja; Kai Leong Lam (International Journal of Biomaterials)
Chitosan nanoparticles (CS NPs) exhibit good physicochemical properties as drug delivery systems. The aim of this study is to determine the modulation of preparative parameters on the physical characteristics and colloidal stability of CS NPs. CS NPs were fabricated by ionic interaction with dextran sulphate (DS) prior to determination of their storage stability. The smallest CS NPs of 353±23 nm with a surface charge of +56.2±1.5 mV were produced when CS and DS were mixed at pH 4 and with a DS : CS mass ratio of 0.5 : 1. An entrapment efficiency of 98% was achieved when BSA/siRNA was loaded into the nanoparticles. The results also showed that particle size and surface charge of CS NPs were slightly changed up to 2 weeks when stored at 4°C. Greater particle size and surface charge were obtained with increasing the concentration of DS. In conclusion, NPs were sufficiently stable when kept at 4°C and able to carry and protect protein.